Client’s Satisfaction toward Communication Skills among Doctors in Primary Health Care Centers in Erbil City (Raparin Journal of Humanities (RJH), 2020)
Back ground and Objectives: Effective communication is important at all steps of human life, most especially in healthcare organizations because it enables good relationships between doctors and clients and helps them in challenging healthcare choices. This study aimed to identify level of satisfaction of clients with communication of doctors in primary health care centers and to find out the association between client’s satisfaction and their socio-demographics.Methods: Quantitative design, cross-sectional descriptive study was conducted to determine the level of client’s satisfaction toward communication skills of doctors in four primary health care centers. The data were collected at the period of 15th of April, 2019 to 1st of July, 2019. So, 300 clients were chosen randomly.Result: The mean age + SD was 35.0 + 10.8 years, ranging from 19 to 70 years. The median was 33 years. The majority (71%) of the clients aged less than 40 years. Around two thirds (64.3%) of the clients were females, and 80.3% of the clients were Muslims. Around one third (34.3%) of the clients attended the PHC centers for immunization, 32% for checkup, and 23% for medical treatment. 34.4% of the clients visit the PHC center more than four times per year, 26% visit the center four times per year, and 25% of the clients visit the center three times per year. There was no significant association between the communication skills of doctors with the following variables: age of the client (p = 0.096), gender (p = 0.315), religion (p = 0.653), educational level (p = 0.615), type of health care services (p = 0.469), and number of visits per year (p = 0.089).Conclusion: study revealed that 26% of clients who were very satisfied with physician’s communication skills, and 36.3% were satisfied, and 6.7 % dissatisfied. There were no significant association between the client satisfactions of doctors with their socio-demographical characteristics.